The History of the emergence and development of self-regulation in Russia - A. Algazina (Правоприменение)
The subject. The study of the Genesis of the emergence and development of any phenomenonallows to know its essence, as well as to make a prediction about the prospects for itsfurther development. Given the importance of self-regulation in the context of the changesin our country, administrative reform, addressing the problems of the Genesis of self-regulationis very timely and relevant.The purpose of the article is to reveal the peculiarities of the emergence and developmentof self-regulation in Russia.Methodology. The methodological basis for the study: general scientific methods (analysis,synthesis, comparison, description); private and academic (comparative legal, interpretation,formal-legal).Results, scope. Under self-regulation this article is to understand the management activitiescarried out by self-regulatory organizations, and consisting in the development and establishmentof standards and rules of professional activity, as well as sanctions for non-complianceor inadequate performance. Based on the author's proposed definition of "self-regulation",the fundamental criterion for the recognition of any organizations the prototypeof the modern self-regulating organizations was selected the purpose of their creation: regulationof activity of subjects of professional activities and the availability of appropriategiven the objectives of the authority. The study of the history of creation and functioningof associations of subjects of professional activity allows to conclude that self-regulation isnot fundamentally new, previously unknown in our country a legal phenomenon.Conclusions. The first prototypes of self-regulatory organizations originated in Russia in theMiddle ages as a voluntary Association of merchants.In the XVIII century found the beginnings of a model of mandatory self-regulation. In thisperiod at the state's initiative used the European experience, was created workshops as anorganizational form of Association of artisans, granting the right to engage in trade.In the Soviet period on the self-regulation can only speak as declaratory of the principle offunctioning of the legal profession.The emergence of self-regulation as a special kind of management activities occurred inRussia in late 1990s – early 2000-ies. The greatest degree of legal regulation-regulationachieved after the adoption of the Law on SRO, established a combination of voluntary andmandatory models of self-regulation.